TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Persulfate-assisted anaerobic digestion systems: advances in microbial electron transport chain reconstruction and metabolic regulation driven by reactive oxygen species - Yingjin Song; Sheng Xu; Yanshan Wang; Lan Mu; Huiling Niu; Qingyi Li; Yinjie Zhong; Yvxing Luo; Zhi Wang; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

A bioinspired flavin-based catalytic construct enabling intracellular NAD+/NADH redox regulation for mitigating skin aging - Jiani Xiang; Qian Ling; Li Yan; Ying Xia; Peizhen Lou; Zhen-Gang Wang; Ting Li; Huiling Wu (Chemical Engineering Journal, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

A successful NaCl reduction strategy: Using spent hen meat hydrolysates to improve the sensory and in vitro digestion properties of sodium-reduced Cantonese sausage - Ruixia Chen; Fidel Toldrá; Junyi Xiang; Huiling Yan; Weizheng Sun; Xiao-Chen Liu (Meat Science, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Relationship between the microplastics in typical marine organisms and the environment: A case study in Bohai Bay, China - Yifan Zheng; Yizhang Zhang; Zhen-Guang Yan; Changyuan Tang; Xutao Wang; Ye Li; Huiling Zhang (Marine Environmental Research, 2026)

Foraminiferal distribution patterns and their ecological implications on Huangyan Island, South China Sea - Min Meng; Shichen Tao; Pamela Hallock; Qi Shi; Hongqiang Yan; Huiling Zhang; Guoquan Qin; Kefu Yu (Marine Geology, 2026)

Total synthesis of the proposed menominin A and its stereoisomers: identification of a highly potent isomer (1a) against RM-1 prostate cancer cells - Yu Jiang; Xin Li; Jiayi Li; Yuhan Xiao; Huiling Xu; Junqiu Zhang; Min-Jing Cheng; Junyang Liu; Jia-Lei Yan (Molecular Diversity, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

VK-RRT*: A Multi-Constraint Coupling Approach to Energy-Efficient AUV Path Planning in Three-Dimensional Ocean Current Environments - Ziming Chen; Jinjin Yan; Huiling Zhang; Xiuyan Peng (Journal of Marine Science and Engineering, 2026)
To address unclear multi-constraint coupling mechanisms, energy estimation errors, and poor dynamic feasibility in autonomous underwater vehicle path planning, this paper proposes an energy-efficient velocity-kinodynamic rapidly exploring random tree star algorithm. The method integrates a velocity–energy model, a velocity–curvature model, and a velocity–safe-distance model into a planning framework. Four targeted improvements are incorporated: a potential-field-guided sampling, an adaptive step-length expansion, a kinodynamic feasibility constraint, and a multi-objective cost function. Simulation experiments across four scenarios and five start–goal tasks show that the proposed method eliminates all curvature violations, reduces propulsion energy by up to 49.4% and improves mean minimum obstacle clearance by 34.2% and 47.4% over the two baselines. Ablation studies confirm that each module contributes to overall performance.

Enhanced adsorption of La(III) and Ce(III) onto phytic acid modified N-(2-hydroxyethyl) acrylamide - Zengjin Fu; Yan Hao; Tingrui Lin; Huiling Ma; Huazheng Sai; Hui Yang (Journal of Water Process Engineering, 2026)

Actinotalea endophytica sp. nov., a Novel Endophytic Actinobacterium Isolated from Sonneratia apetala - Huiling Tang; Zhouqing Zheng; Mingsheng Chen; Xiaohui Chen; Dongqiang Yan; Hong Li; Li Tuo; Feina Li (Current Microbiology, 2026)

Nitrogen addition accelerates soil nitrogen transformation processes by influencing plant-mediated microbial pathways on semi-arid plateau grassland - Furong Wei; Benshuai Yan; Chunxiao Wu; Huiling Wang; Guozhen Gao; Guoliang Wang (Plant and Soil, 2026)

Aroma enhancement in clay jar-aged wine: 2-acetyl-1H-pyrrole at subthreshold modulates perception of fruity esters - Yue Ma; Getu Shi; Xiaoju Tian; Huiling Zhang; Yan Xu; Ke Tang (Food Chemistry, 2026)

Characterization and application of soybean hull dietary fiber as a fat replacer in low-fat ice cream - Huiling Yan; Wenjing Zhang; Zhaoxiang Ma; Shanan Chen; Hui Zhang; Jie Xiao; Elke Scholten; Mingchun Lv; Xiangyu Liu; Yuan Li (Food Hydrocolloids, 2026)

Distinct Roles of Walnut JrPPO1 and JrPPO2 in Plant Stress Responses Revealed Through Fruit Assays and Heterologous Expression in Arabidopsis thaliana - Yifan Wang; Md Rasel; Yan Tang; Zhipeng Guo; Nan Wang; Niu Ye; Huiling Ma (Journal of Plant Growth Regulation, 2026)

Rapid starch degradation characterized by the related gene expression and key enzymes resulted in an optimum comprehensive quality of sugar, acid, and firmness in postharvest apples - Lingyu Qiu; Niu Ye; Yang Zhao; Mengke Cao; Miaomiao Ge; Xiaolin Ren; Yan Tang; Huiling Ma (Postharvest Biology and Technology, 2026)

Real-time prediction and reconstruction of hydrofoil structural stress using machine learning - Yu Ao; Pengyu Lv; Yuqing Hou; Jiale Yan; Di Peng; Yimin Zhang; Changrong Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2026)

Elucidating microplastic adsorption mechanisms in biomass composite materials through interpretable machine learning - Huiling Li; Yimin Shi; Junhao Liu; Zhichen Ba; Shengkai Liu; Birong Yan; Daxin Liang; Yanjun Xie (Journal of Hazardous Materials, 2026)

Phenyllactic acid inhibits softening, lignification and quality deterioration of postharvest pea sprouts - Huiling Yan; Mengying Xia; Qingxia Liao; Ludong Huang; Wanjie Li; Tian Yao (Postharvest Biology and Technology, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Revealing the regulatory mechanisms of amino acids in co-fermentation of jujube pulp by Lachancea thermotolerans and Lactiplantibacillus plantarum: insights from flavor characterization and metabolomic analysis - Zijian Gong; Kangxue Chen; Yufei Zhang; Ruyu Shangguan; Huiling Li; Yi Yan; Caiyun Wu; Hongjie Lei (Food Research International, 2025)

Retraction notice to ‘Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis’ [Environ. Res. 241 (2024) 117474] - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2025)

Coral-inferred high seasonal sea surface temperature in the South China Sea at 7.4 thousand years ago - Shichen Tao; Kam-biu Liu; Hongqiang Yan; Min Meng; Chun-Yuan Huang; Chuan-Chou Shen; Huiling Zhang; Kefu Yu; Qi Shi (Earth and Planetary Science Letters, 2025)

Regulating A-site elements to boost ultra-low-temperature selective catalytic reduction of NOx on AFeMnO5 catalysts - Junhao Liu; Jingyi Zhu; Ying Yan; Huifang Cheng; Huiling Zheng; Yun Wang; Huaming Li; Jian Liu; Jixing Liu (Chemical Engineering Journal, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Transcriptome analysis reveals regulatory processes of transcription factors on anthocyanin accumulation in the bark of Populus simonii × P. nigra - Meiqi Lu; Quyen Quynh Thi Lai; Xinyu Wang; Song Chen; Siyuan Li; Yuanfu Liu; Zhanchen Ren; Huiling Yan; Qiushuang Zhao; Haoran Bao; Ling Jin; Yunxia Wei; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

CSPNet: A feature interaction network for tomato leaf disease detection in complex scenarios - Chunman Yan; Huiling Li (Computers and Electronics in Agriculture, 2025)

Analysis of nitrogen effects on starch characteristics of Japonica rice from northern China through flow cytometry - Bingchun Yan; Xuanming Wang; Yuqi Liu; Yuzhuo Liu; Min Zhong; Xue Wan; Ya Liu; Hongfang Jiang; Songting Liu; Huiling Liu; Qingchun Ma; Yanze Zhao; et al. (Food Chemistry, 2025)

Comprehensive assessment of full-cycle high-solid anaerobic digestion of straw for methane production update: Focus on performance improvement and circular economy - Yingjin Song; Yinjie Zhong; Yanshan Wang; Lan Mu; Yuxing Luo; Sheng Xu; Huiling Niu; Zhi Wang; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

In-situ pH regulation of biomass-based hydrogel composite: A green approach to efficient lithium ion capture from salt lake brine - Shengkai Liu; Chunling Cao; Huiling Li; Wenxuan Wang; Birong Yan; Junreng Liu; Wei Wang; Tai Peng; Daxin Liang; Yanjun Xie (Chemical Engineering Journal, 2025)

Enrichment of Feammox microflora utilizing in-situ iron in excess activated sludge: substrate metabolism, gene variation, and microbial communities - Maoxia Chen; Jing Ru; Yan Yi; Yang Li; Liang Wu; Huiling Jiang (Bioresource Technology, 2025)

Insights into the impacts of diverse electron acceptors on perfluorooctanoic acid and perfluorooctane sulphonic acid removal in sediment - Huiling Sun; Liwei Zhang; Junfan Yao; Jiaqi Zhang; Tianyu Wang; Guangzhou Yu; Yan Kang; Haoqin Ma; Shaoping Kuang; Zizhang Guo; Xiaohan Jiang (Journal of Environmental Chemical Engineering, 2025)

Efficient removal of ciprofloxacin via photo-Fenton system under circumneutral condition: Performance and mechanism insight - Yongxia Du; Yan Xiao; Yin Xu; Wenzhuo Zhang; Jiahao Feng; Wenwen Zhao; Huiling Tang; Xiaomeng Hai; Jing Xu; Ivan P. Pozdnyakov; Hui Zhang (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Analysis of nitrogen effects on starch characteristics of Japonica rice from northern China through flow cytometry” [Food Chem. 492(Part 1) (2025) 145344] - Bingchun Yan; Xuanming Wang; Yuqi Liu; Yuzhuo Liu; Min Zhong; Xue Wan; Ya Liu; Hongfang Jiang; Songting Liu; Huiling Liu; Qingchun Ma; Yanze Zhao; et al. (Food Chemistry, 2025)

Unlocking the recycling potential of dysprosium for balancing supply and demand across Chinese provinces - Yan-Fei Liu; Qiance Liu; Can Wang; Hongyan Zhang; Zizhan Chen; Daxing Xu; Huiling Song; Mingxuan Zhao; Zhongkui Han (Journal of Cleaner Production, 2025)

Optimized cryopreservation of embryogenic tissue of Picea abies based on differential scanning calorimetry - Jiwen Hu; Ziyan Pu; Chunhui Hao; Huiling Yan; Shumei Qian; Tianqing Zhu; Wenjun Ma; Sanping An; Lisheng Kong; Junhui Wang (Cryobiology, 2025)

Loss of soil fauna following conversion of subtropical natural forests - Huihui Wen; Koenraad Van Meerbeek; Huiling Zhang; Yan Peng; Kai Yue; Xiangyin Ni; Danni Qiu; Zihao Chen; Roland Bol; Fuzhong Wu (Soil Ecology Letters, 2025)

Environmental, social responsibility and corporate governance (ESG) characterized industry evaluation system, factors and benefits -- evidence from the grounded theory of noise prevention and control concept stocks in China - Desheng Zhang; Botao Yan; Huiling Zhang (Environment, Development and Sustainability, 2025)

Advanced exploration of metabolite variation and the role of key differential metabolites during the ripening process of PSE pork - Linyuan Shen; Yuhang Lei; Tianci Liao; Kai Wang; Huiling Zhang; Haifeng Dan; Lili Niu; Ye Zhao; Lei Chen; Yan Wang; Li Zhu; Mailin Gan (Food Chemistry, 2025)

Recent advances in heteroatom doping for performance optimization of inorganic metal-based lithium-ion adsorbents - Birong Yan; Shengkai Liu; Yimin Shi; Huiling Li; Xi Li; Yonggui Wang; Yabei Xu; Wei Wang; Tai Peng; Daxin Liang; Yanjun Xie (Desalination, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Syringa oblata maintains rhizosphere r-strategists and microbial functions by regulating exudates in root tip zone under drought - Huiling Wang; Jiarui Chen; Hang Jing; Benshuai Yan; Furong Wei; Sha Xue; Guoliang Wang (Applied Soil Ecology, 2025)

Super paleo-typhoons striking southern Hainan Island in the northern South China Sea during the mid-late Holocene: Coral boulder evidence from a fringing reef - Shengnan Zhou; Qi Shi; Shichen Tao; Xiyang Zhang; Hongqiang Yan; Huiling Zhang; Zhiwei Hou; Wenlong Jing; Ji Yang (Global and Planetary Change, 2025)

Key functional guilds with high trophic level organisms in soil are vital contributors to greenhouse gas emissions from cropland - Zhiyuan Yao; Huiling Hu; Tao Wang; Xiaoguo Wang; Yulong Li; Xiaoming Sun; Sina Adl; Fangfang Yan; Yingjie Zhang; Bo Zhu (Agriculture, Ecosystems & Environment, 2025)

Data-driven optimization of nose profiles for water entry impact load reduction - Kai Lv; Enfan Lin; Yongze Liu; Zongbao Chen; Yexian Wang; Ming He; Jiale Yan; Pengyu Lv; Yantao Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2025)

Iron-doped titanium lithium-ion Sieves@Sodium alginate-enhanced carboxymethyl cellulose aerogels: A synergistic leap in adsorption and sustainability - Shengkai Liu; Birong Yan; Yu Han; Wei Wang; Yimin Shi; Yonggui Wang; Huiling Li; Junhao Liu; Zefang Xiao; Daxin Liang; Yanjun Xie (Journal of Cleaner Production, 2025)

An update of aurones: food resource, health benefit, biosynthesis and application - Jiali Yang; Zhengjiao Gao; Zhiqian Yu; Yu Hou; Dingtao Tang; Huiling Yan; Fuwang Wu; Sui Kiat Chang; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

The history of the El Niño–Southern Oscillation and sea surface salinity during 1376–1500 CE reconstructed by Porites coral δ18O from Huangyan Island, South China Sea - Shichen Tao; Kam-biu Liu; Hongqiang Yan; Min Meng; Kefu Yu; Qi Shi; Huiling Zhang (Global and Planetary Change, 2024)

Pyridoxal phosphate promotes the γ-aminobutyric acid accumulation, antioxidant and anti-hypertensive activity of germinated tartary buckwheat - Huiling Yan; Hongxu Chen; Juan Liu; Tian Yao; Mengying Xia; Qingxia Liao; Ludong Huang; Wanjie Li; Yu Song; Lianxin Peng; Jianglin Zhao; Liang Zou; et al. (Journal of Cereal Science, 2024)

A point-of-care testing strip based on a rationally designed antigen and antibody for fast and reliable Diquat poisoning detection: Ready for clinical application - Shun Zhang; Guanyan Fu; Weijing Yi; Jiahui Zhou; Wenbin Liang; Wanjiang Zhao; Tian Zhang; Gen Zhang; Jing Zhang; Huiling Li; Huifang Yan; Banghua Wu; et al. (Chemical Engineering Journal, 2024)

Identification and transcriptome analysis of a photosynthesis deficient mutant of Populus davidiana Dode - Xinyu Wang; Yan Zhou; Song Chen; Meiqi Lu; Chunyu Guan; Ruihan He; Yue Yu; Huiling Yan; Wenxuan Liu; Siyuan Li; Yuanfu Liu; Kanglei Li; et al. (Plant Science, 2024)

Carbon budgets of coral reef ecosystems in the South China Sea - Hongqiang Yan; Qi Shi; Lijia Xu; Huiling Zhang; Meixia Zhao; Shichen Tao (Frontiers in Marine Science, 2024)
The coral reef ecosystem is one of the most productive ecosystems in the ocean, and is also an important calcium carbonate deposition region. Because excess production is very low in coral reefs, organic carbon reservoirs are very limited. During the calcification process, each mole of CaCO 3 will produce 1 mol of CO 2 , approximately 60% of which will be released into the atmosphere through the sea-air interface. This causes coral reefs to be large inorganic carbon reservoirs, but at the same time, most coral reefs act as atmospheric CO 2 sources (which also act as sinks in some coral reefs). Therefore, clarifying the sea-air CO 2 exchange flux and carbon storage is critical for understanding the carbon cycle in coral reef ecosystems. In this paper, we summarize the carbon cycle processes in the coral reefs of the South China Sea (SCS) and estimate the total CO 2 budget and carbon reserves. According to current research, the coral reefs in this area act as a source of atmospheric CO 2 , releasing 0.37−1.59 × 10 11 g C a -1 into the atmosphere. Owing to their extremely high biological productivity and carbonate productivity, the carbon reserves of coral reefs in the SCS range from 1.66–3.78 × 10 12 g C a -1 , which is an order of magnitude greater than the CO 2 emissions at the sea–air interface. Overall, coral reefs in the SCS are important carbon storage areas. As the current results are still approximate, a more comprehensive and in-depth investigation is needed to clarify the carbon source/sink processes, regulatory mechanisms, and carbon storage capacity of SCS coral reefs.

Construction of a double-increasing emission fluorescent probe and its application in food detection of benzoyl peroxide and biosystem imaging - Huiling Zhang; Weina Yan; Can Xie; Kun Luo; Liyi Zhou (Food Chemistry, 2024)

Palygorskite supported nanometer spherical Fe2O3 composite as an effective photocatalyst for peroxymonosulfate activation: Promotion of the Fe(III)/Fe(II) cycle by photogenerated electrons under visible light - Huiling Tang; Yin Xu; Weiping Tang; Yan Xiao; Chi Zhang; Jing Xu; Ivan P. Pozdnyakov; Hui Zhang (Chemical Engineering Journal, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

Microplastics emerge as a hotspot for dibutyl phthalate sources in rivers and oceans: Leaching behavior and potential risks - Lujian Lin; Bo Yuan; Huiling Liu; Yue Ke; Weifeng Zhang; Hanyi Li; Haoliang Lu; Jingchun Liu; Hualong Hong; Chongling Yan (Journal of Hazardous Materials, 2024)

Amelioration of radiation cystitis by tetrahedral framework nucleic acid nanostructures functionalized with quercetin - Wei Wang; Ran Yan; Lede Lin; Liao Peng; Yang Xiong; Huiling Chen; Xiaoshuai Gao; Kun Liu; Liang Zhou; Yunfeng Lin (Chemical Engineering Journal, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

SST and ENSO activity 282,000 years ago reconstructed from Porites coral in the South China Sea - Shichen Tao; Kam-biu Liu; Hongqiang Yan; Min Meng; Huiling Zhang; Yi Wu; Kefu Yu; Qi Shi (Global and Planetary Change, 2024)

Measurement of Elastic Bi-modulus of Rock-type Materials: Insight from comparative and parallel tests - Yan Zhang; Hao Zheng; Huiling He; Peng Sha; Linlin Wang; Shengwen Qi; Xiaolin Huang; Jianhong Ye (Bulletin of Engineering Geology and the Environment, 2024)

Characterization of a Homeodomain-Leucine Zipper Gene 12: Gene Silencing in Pepper and Arabidopsis-Based Overexpression During Abiotic Stress - Ruixing Zhang; Quanhui Li; Jingjing Xiao; Saeed ul Haq; Abid Khan; Guoxin Cheng; Huiling Yan; Zhenhui Gong (Journal of Plant Growth Regulation, 2024)

Controlled atmosphere storage alleviates the browning of walnut (Juglans regia L.) fruit through enhancing GABA-mediated energy metabolism - Niu Ye; Dongli Zhang; Shan Liu; Yongqi Zhang; Yifan Wang; Yan Tang; Xiangna Yang; Jiahao Chai; Yanping Ma; Huiling Ma (Postharvest Biology and Technology, 2024)

On in-plane crushing behavior of an improved double-arrow auxetic metamaterial with two-step deformation mode - Wei Zhang; Zhi Yan; Jing Zhang; Huiling Wang; Fang Han; Pei Jiang; Tianxing Wu; Qinghua Qin (Engineering Structures, 2024)

Rotenone impairs brain glial energetics and locomotor behavior in bumblebees - Jieteng Chen; Xiaohuan Mu; Huiling Liu; Qiyao Yong; Xiaoman Ouyang; Yan Liu; Li Zheng; Hao Chen; Yifan Zhai; Jie Ma; Liang Meng; Shanshan Liu; et al. (Science of The Total Environment, 2024)

RETRACTED: Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2024)

N addition affects the heterotrophic respiration of bulk and rhizosphere soils through changes in root traits and C-degrading functional genes in semi-arid grassland - Furong Wei; Benshuai Yan; Chunxiao Wu; Huiling Wang; Guoliang Wang (Plant and Soil, 2024)

Metabolomic and transcriptomic integrated analysis revealed the decrease of monoterpenes accumulation in table grapes during long time low temperature storage - Huiling Wang; Xiaoyue Wang; Ailing Yan; Zhenhua Liu; Jiancheng Ren; Haiying Xu; Lei Sun (Food Research International, 2023)

Long-term application of nitrogen and phosphorus fertilizers changes the process of community construction by affecting keystone species of crop rhizosphere microorganisms - Chunxiao Wu; Benshuai Yan; Furong Wei; Huiling Wang; Liqiang Gao; Huizhen Ma; Qing Liu; Ying Liu; Guobin Liu; Guoliang Wang (Science of The Total Environment, 2023)

Changes in soil microbial activity and their linkages with soil carbon under global warming - Hongwei Xu; Lulu Huang; Jun Chen; Huiling Zhou; Yan Wan; Qing Qu; Minggang Wang; Sha Xue (CATENA, 2023)

Persulfate promoted visible photocatalytic elimination of bisphenol A by g-C3N4–CeO2 S-scheme heterojunction: The dominant role of photo-induced holes - Yin Xu; Xin Tang; Yan Xiao; Huiling Tang; Heng Lin; Yujuan Lv; Hui Zhang (Chemosphere, 2023)

CCE and EODF as two distinct non-shivering thermogenesis models inducing weight loss - Tianyi Xu; Juan Wang; Hongwei Shi; Xiaofang Wei; Huiling Zhang; Yunyan Ji; Shiting Lu; Yi Yan; Xiuju Yu; Xiaomao Luo; Haidong Wang (Pflügers Archiv - European Journal of Physiology, 2023)

A 3D phytic acid cross-linked high-porous conductive hydrogel integrating g-C3N4 for electrochemical multiplex sensing of heavy metal ions - Lu Xiao; Yulan Zhao; Gang Chang; Huiling Yan; Rong Zou; Xiuhua Zhang; Shengfu Wang; Hanping He (Analytica Chimica Acta, 2023)

Histone demethylase MaJMJ15 is involved in the regulation of postharvest banana fruit ripening - Jing Zeng; Guoxiang Jiang; Hanzhi Liang; Huiling Yan; Xiangjin Kong; Xuewu Duan; Zhiwei Li (Food Chemistry, 2023)

The Complete Genome Sequence of a Gossypol-Degrading Bacterial Strain, Raoultella sp. YL01 - Si Chen; Weishu Zhang; Huiling Zhang; Ying Cui; Feng Wang; Jing Wu; Hongjun Chao; Dazhong Yan (Current Microbiology, 2023)

The removal of antibiotic, antibiotic resistant bacteria and genes in persulfate oxidation system via activating by antibiotic fermentation dregs derived biochar - Yafei Wang; Chenhao Wang; Shen Yan; Yingchun Li; Chen Cai; Huiling Liu; Peng Ren; Mengmeng Wang; Shaoping Kuang (Journal of Cleaner Production, 2023)

Postharvest H2O2 treatment affects flavor quality, texture quality and ROS metabolism of ‘Hongshi’ kiwifruit fruit kept at ambient conditions - Huiling Yan; Hongxu Chen; Jianglin Zhao; Tian Yao; Xiaochun Ding (Food Chemistry, 2023)

NIR-responsive hollow germanium nanospheres mediate photothermal/photodynamic therapy and restrain immunosuppression to cooperatively eradicate primary and metastatic tumors - Qilin Li; Huiling Fan; Yunruo Xu; Miaodeng Liu; Jia Liu; Luming Xu; Meizhen Zou; Qian Cheng; Yan Zhang; Tao Liang; Lin Shi; Xianluo Hu; et al. (Chemical Engineering Journal, 2023)

Abundant bacteria and fungi attached to airborne particulates in vegetable plastic greenhouses - Changliang Nie; Xueyun Geng; Huiling Ouyang; Lina Wang; Zongzhen Li; Mingyu Wang; Xiaomin Sun; Yan Wu; Yunhan Qin; Youxin Xu; Xu Tang; Jianmin Chen (Science of The Total Environment, 2023)

Human Umbilical Cord-Derived Mesenchymal Stem Cells Ameliorate Skin Aging of Nude Mice Through Autophagy-Mediated Anti-Senescent Mechanism - Ting Li; Li Zhou; Mengqiang Fan; Zuxiang Chen; Li Yan; Haishan Lu; Ming Jia; Huiling Wu; Letian Shan (Stem Cell Reviews and Reports, 2022)

Analysis on characteristics of female gametophyte and functional identification of genes related to inflorescences development of Kentucky bluegrass - Jinqing Zhang; Huiling Ma; Yan Liu (Protoplasma, 2022)

Deep electrical structure and dynamic mechanism of the Yinchuan Graben on the western margin of the Ordos Block - Gang Min; Bingxi Yin; Jinchao Chen; Yong Yang; Huiling Yuan; Yan Wang (Geosciences Journal, 2022)

Correction to: Association Study Between Genetic Variation in Whole Mitochondrial Genome and Ischemic Stroke - Yingying Luan; Dongzhi Yang; Zhaojing Zhang; Xiaoshuai Bie; Huiling Zhao; Yuanli Wang; Yang Liu; Shangdong Yang; Baixue Zhou; Yan Xu; Hong Zheng; Ying He (Journal of Molecular Neuroscience, 2021)

Association Study Between Genetic Variation in Whole Mitochondrial Genome and Ischemic Stroke - Yingying Luan; Dongzhi Yang; Zhaojing Zhang; Xiaoshuai Bie; Huiling Zhao; Yuanli Wang; Yang Liu; Shangdong Yang; Baixue Zhou; Yan Xu; Hong Zheng; Ying He (Journal of Molecular Neuroscience, 2021)

Whole-genome sequence analysis of the 24th genotype D11 of measles virus - Huiling Wang; Jinhua Song; Wenbo Xu; Yan Zhang (Archives of Virology, 2020)

Protective effects of hederagenic acid on PC12 cells against the OGD/R-induced apoptosis via activating Nrf2/ARE signaling pathway - Huankai Yao; Yeling Liu; Guihua Zhu; Yinyin Duan; Huiling Wu; Yan Li (Medicinal Chemistry Research, 2020)

Sikokianin A from Wikstroemia indica protects PC12 cells against OGD/R-induced injury via inhibiting oxidative stress and activating Nrf2 - Huankai Yao; Wenting Zhang; Huiling Wu; Ming Yang; Pengxiang Wei; Hang Ma; Jingyu Duan; Chunping Zhang; Yan Li (Natural Product Research, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Pretreatments with injured microenvironmental signals altered the characteristics of human umbilical cord mesenchymal stem cells - Huiling Cao; Qian Hui; Yongmin Yan; Chunbing Zhang; Xuewen Yang; Liang Ge; Wenrong Xu (Biotechnology Letters, 2016)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Mechanical stress induces neuroendocrine and immune responses of sea cucumber (Apostichopus japonicus) - Jie Tan; Fenghui Li; Huiling Sun; Fei Gao; Jingping Yan; Chunlei Gai; Aihua Chen; Qingyin Wang (Journal of Ocean University of China, 2015)

Immunogenicity of the capsid precursor and a nine-amino-acid site-directed mutant of the 3C protease of foot-and-mouth disease virus coexpressed by a recombinant goatpox virus - Wenge Ma; Jie Wei; Yurong Wei; Huiling Guo; Yinghong Jin; Ying Xue; Yan Wang; Zhong Yi; Liya Liu; Jiong Huang; Lijian Wang (Archives of Virology, 2014)

Bacterial diversity of gut content in sea cucumber (Apostichopus japonicus) and its habitat surface sediment - Fei Gao; Jie Tan; Huiling Sun; Jingping Yan (Journal of Ocean University of China, 2014)

Screening of candidate proteins interacting with IE-2 of Bombyx mori nucleopolyhedrovirus - Yejun Wu; Yu Wu; Yan Wu; Hui Tang; Huiling Wu; Guozheng Zhang; Wenbing Wang (Molecular Biology Reports, 2013)

Characterization of the open reading frame 7a from Bombyx mori nucleopolyhedrovirus - Yong Liu; Feng Yu; Huiling Wu; Qing Cao; Yu Wu; Yan Wu; Wenbing Wang (Molecular Biology Reports, 2013)

Effect of yeast polysaccharide on some hematologic parameter and gut morphology in channel catfish (Ictalurus punctatus) - Huiling Zhu; Huiyu Liu; Jing Yan; Rui Wang; Lihe Liu (Fish Physiology and Biochemistry, 2012)

Two centuries-long records of skeletal calcification in massive Porites colonies from Meiji Reef in the southern South China Sea and its responses to atmospheric CO2 and seawater temperature - Qi Shi; KeFu Yu; TianRan Chen; HuiLing Zhang; MeiXia Zhao; HongQiang Yan (Science China Earth Sciences, 2012)

Eukaryotic translation elongation factor 1 delta inhibits the ubiquitin ligase activity of SIAH-1 - Huiling Wu; Yan Shi; Ying Lin; Wei Qian; Yao Yu; Keke Huo (Molecular and Cellular Biochemistry, 2011)

Mesenchymal stem cells derived from human umbilical cord ameliorate ischemia/reperfusion-induced acute renal failure in rats - Huiling Cao; Hui Qian; Wenrong Xu; Wei Zhu; Xu Zhang; Yuan Chen; Mei Wang; Yongming Yan; Ying Xie (Biotechnology Letters, 2010)

Human SMAD4 is phosphorylated at Thr9 and Ser138 by interacting with NLK - Yan Shi; Kan Ye; Huiling Wu; Yixing Sun; Huili Shi; Keke Huo (Molecular and Cellular Biochemistry, 2010)

Hepatocellular carcinoma-associated gene 2 interacts with MAD2L2 - Li Li; Yan Shi; Huiling Wu; Bingbing Wan; Pu Li; Li Zhou; Huili Shi; Keke Huo (Molecular and Cellular Biochemistry, 2007)

Identification of pronp1, a tobacco profilin gene activated in tip-growing cells - Ines Swoboda; Prem L. Bhalla; Huiling Xu; Yan Zhang; Irene Mittermann; Rudolf Valenta; Mohan B. Singh (Plant Molecular Biology, 2001)